Design and fabrication of high productive barbecue machine - Ghani, Usman; Hayat, Mubashir; Habib, Tufail; Zeb, Alam; Azam, Khizar (International Journal of Engineering and Technology, 2020)
Conventional methods to use a metal cavity having charcoal assisted with skewers in getting the final barbecue encounter a lot of limitations such as time, lower productivity, single temperature heating, worker fatigue, controlling of heat and time, energy consumption, importability, unhygienic food preparation (road-side open barbecuing) and cost-effectiveness etc. The proposed research considers the design and fabrication of barbecue machine fueled with gas and actuated by electrical cum mechanical systems. This electromechanical semi-automatic barbecue machine overcomes the stated limitations. It will be an important tool used for household as well as commercial use. This machine capacity is to barbecue an average of 4.5 kg of meat at a time. The machine is divided into three chambers. In first chamber barbecue is kept on lower temperature for high time. Once it completes its first stage motor attached with chain drive mechanism is activated and it brings the food to second chamber. In the second chamber, it takes lower time on high temperature and when it finishes it is conveyed to first chamber for un-feeding. The aim of this research is also to commercialize the product in the market targeting small scale industries and people involved in road side barbecue production, restaurants and other organizations.Â Â